Genomic reduction at TTC repeats in the bacterial genome of treated cases of Hansen's disease: A possible survival mechanism of Mycobacterium leprae - Abu Hena Hasanoor Reja; Abhishek De; Pradip Kumar Patra; Supratik Biswas; Umesh Duttagupta; Amrita Sil; Nibir Biswas; Surajita Bannerjee; Aarti Sarda; Basudev Bhattacharya (Wolters Kluwer Medknow Publications, 2018)
Introduction: Mycobacterium leprae has a small genome and a tendency of persisting as a very low-grade infection. The authors have shown earlier, that the changes in TTC repeats, in M. leprae genome may contribute to the restriction of the pathogenicity of the bacterium and its survival strategy in case of pure neural Hansen's disease. We suspect, that a similar genomic reduction if happens in treated cases of Hansen's disease, can be a determining factor for developing persisters and relapse. Aim: The present study aimed to find out if there was any evidence of genomic reduction in treated cases of Hansen's disease that showed microbiological nonresponse. Methods: Skin biopsies were taken from treated cases of Hansen's disease at tertiary centers in Kolkata and at Raipur who had bacterial index (BI) unchanged or increased compared to their pretreatment BI. Analysis for the mutation in rpoB gene and folP1 gene were done to rule out rifampicin and dapsone resistance, respectively. The entire TTC repeat region of the bacteria was amplified by polymerase chain reaction and was subjected to sequencing. The obtained sequences were then analyzed by CLUSTALW. Results: A total of 127 patients were included in the study of which in 52 the BI remained same and 75 had an increase in BI, even after 6 months of completion of multidrug therapy. Among the samples, 2 had positive rpoB gene mutation. No mutation was found in the folP1 gene. The TTC repeat of both the rpoB-resistant samples was found to have 17 copies, which matched their pretreatment copy number. In other 125 cases, 60 cases showed no change from their pretreatment TTC number. Of those 65 samples that showed evidence of genomic reduction, 11 samples showed one copy, 41 showed 2 copies, and 13 showed 3 copies deletion. We also observed a significant regional variation. Conclusion: We concluded that there was evidence of genomic reduction, which might lead to microbiological nonresponse in treated cases of Hansen's disease. This indicated a possibility of future persistence and relapse.